Impact of tutoring of degree works on scientific production in university environments - Flores-Pacheco, Juan Asdrúbal (Revista Universitaria del Caribe, 2023)
After the completion of the different academic components of the degree training programs (bachelor's degrees or their equivalents), it is customary to present a culmination of studies, in most cases they are monographs, theses and the like. Equally important to the technical and methodological compliance with this document is the correct selection of the guiding teacher, called tutor/advisor. Under this assumption, this essay explores the etymological and conceptual definition of the function of the academic tutor of undergraduate work. The main typologies of attitudinal behavior of academics and scientists who assume this responsibility are also described. It should not be ignored that the lack of methodological and pedagogical orientation, as well as the endogamy assumed unconsciously due to the lack of generational replacement policies, are unfavorable factors for educational quality processes. Situations such as those addressed are topics made invisible by Higher Education Institutions that, in the entirety of their training, must also monitor and train their teachers as a linking element with the learners.